The prophylactic effect of hydroxychloroquine on the severity of COVID-19 infection in an asymptomatic population: A randomized clinical trial - Arezoo Chouhdari (Shahid Beheshti University of Medical Sciences, 2024)
Background: Laboratory and observational data suggest that hydroxychloroquine (HCQ) has biological activity against SARS-CoV-2, potentially permitting its use for disease prevention. This study aimed to evaluate the hydroxychloroquine effect as prophylaxis for SARS-CoV-2 infection. Methods: This double-blind randomized controlled trial was performed on 1000 people between 18-65 who were not suspected of having COVID-19 symptoms at the time of enrollment and had no positive COVID-19 virus test. Hydroxychloroquine or placebo tablets (800 mg/d for the first day followed by 200 mg/d for 6 weeks) were prescribed randomly for participants in 2 groups and followed for 10 weeks. Results: Among 871 participants who were followed within 10 weeks 97(11.1%) became SARS-CoV-2 positive. there were statistically significant differences between infected or non-infected in the hydroxychloroquine (36 of 97 [37.1%]) and placebo (61 of 97 [62.9 %]) groups with a risk ratio of 2.1 (95% confidence interval (CI) 1.01 - 3.21; p = 0.005). The incidence of severe forms of COVID-19 (i.e., hospitalized in the coronavirus ward or the ICU) was 2 of 97 (0.02 %) in participants who received a placebo compared to hydroxychloroquine. The proportion of non-infected people who received hydroxychloroquine prophylaxis was nearly twice higher than that of placebo users (1.87, 95% CI: 1.19 - 2.84, p = 0.05). There were no significant differences between the two groups regarding side effects (1.1% vs. 0.9%), and no severe adverse reactions were observed. Conclusion: Pre-exposure therapy with hydroxychloroquine appears to prevent moderate and severe illness caused by COVID-19 in asymptomatic persons.